Penerapan Metode SS (Sheethalakshmy–Srinivasan) dalam Optimasi Masalah Transportasi untuk Meminimalkan Biaya Distribusi - Yazid Halim, Ahmad; Affandi, Pardi (Equiva Journal, 2025)
The transportation problem is one of the important problems in operations research related to the distribution of goods from several sources to several destinations at minimum cost. This problem aims to determine the number of goods that must be shipped from each source to each destination so that all demand is met with the lowest possible total distribution cost. This study applies the SS Method (Sheethalakshmy–Srinivasan) as a direct approach to solving transportation problems without the need to determine a feasible initial solution. The SS Method offers systematic steps through row and column reduction processes and cost reduction calculation to obtain optimal solutions for both balanced and unbalanced transportation cases. The results of the application of this method show that the SS Method is able to provide optimal solutions efficiently with a shorter calculation time compared to conventional methods such as North West Corner, Least Cost, and Vogel's Approximation. Thus, the SS Method can be used as an effective alternative in optimizing distribution costs in modern logistics systems.